Helicobacter Pylori Positivity in Patients with Hyperemesis Gravidarum - Emel Ebru Özçimen; Ayla Üçkuyu; Işık Üstüner; Filiz Fatma Yanık; Sevsen Kulaksızoğlu; Mesut Öktem; Derya Eroğlu; Esra Kuşçu (Medical Network, 2006)
OBJECTIVE: To investigate the relationship between Helicobacter pylori (H. py lori) infection and hyperemesis gravidarum (HG) by using H. pylori specific serum antibody test and H. pylori stool antigen (HpSA). MATERIAL AND METHODS: This prospective cross-sectional study was carried out on 70 pregnant women with HG and 70 healthy pregnant women. Serum immunoglobulin G antibody for H. pylori and HpSA were assayed in both groups. Chi-square test was used f or statistical analysis. RESULTS: The study and control groups were matched regarding the maternal age, gestational weeks, gravida and parity. Positive serum IgG concentrations were found in 35 of the 70 HG patients (50%) compared with 33 of 70 controls (47.1%), (p>0.05). The rate of HpSA positivity was 32.8% (23/70) and 21.4% (15/70) respectiv ely (p>0.05). CONCLUSION: Contradicting with most of the studies which investigated the relationship between H. pylori infection and HG, our results indicate no significant relationship between HG and H. pylori IgG and HpSA.